De José Joaquim da Rocha a Frederich Wagner: Civilização, nativos e colonos nas representações cartográficas dos sertões leste de Minas Gerais (1778-1855) - Luis Gustavo Molinari Mundim (2009)
For many years the hinterlands of eastern Minas Gerais was considered as a wild region. There are several reports which pointed to barbaric and ignoble character of the natives who lived there. However, from the last quarter of the Eighteenth Century and throughout the Nineteenth Century, the interest of the colonial authorities and settlers in the area arouse gradually. So it began to be explored in a more systematic and expressive way. Several actions were taken in order to incorporate and settle the region. The production of cartographic records was one of those actions and served both as an instrument of knowledge as a means of appropriation of that space. The survey was intended to observe the changes in the representations of the region, especially in cartographic production. These changes involved the legitimacy of the monarchy power on the area and were so intense, both in material and symbolic terms.